2017
DOI: 10.4236/ojog.2017.79099
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Preterm Birth at the Postnatal Ward of Kenyatta National Hospital, Nairobi, Kenya

Abstract: Background: Preterm birth, delivery prior to 37 completed weeks or 259 days gestation, is a worldwide maternal and perinatal challenge and is a leading cause of neonatal morbidity and mortality. Preterm birth remains the leading cause of perinatal and postnatal mortality and morbidity especially in developing countries where the health care services are suffering from limited resources. Premature babies usually suffer from both immediate and long term consequences. Right after birth, they have difficulties in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
8
14
2
Order By: Relevance
“…Those women who experienced PIH were more likely to have PTB. This result is in agreement with result of studies conducted in Ethiopia and other countries [ 58 , 62 , 63 ]. This might be due to reduction of the utero-placental blood floor by hypertension leading to intrauterine growth restriction finally causing preterm birth.…”
Section: Discussionsupporting
confidence: 93%
“…Those women who experienced PIH were more likely to have PTB. This result is in agreement with result of studies conducted in Ethiopia and other countries [ 58 , 62 , 63 ]. This might be due to reduction of the utero-placental blood floor by hypertension leading to intrauterine growth restriction finally causing preterm birth.…”
Section: Discussionsupporting
confidence: 93%
“…Presence of malaria was associated with PTB as evidenced by the pooled analysis of four studies (AOR 3.08; 95% CI: 2.32-4.10) [42,44,79,83]. The pooled analysis of two studies identified that UTI was significantly associated with PTB (AOR 5.27; 95% CI: 2.98-9.31) [37,64] (Fig. 5).…”
Section: Medical Conditionsmentioning
confidence: 85%
“…The presence of chorio-amnionitis (AOR 3.8; 95% CI: 1.3-10.8) [72] and placenta praevia was correlated with PTB (ARR 3.30, 95% CI: 1.34, 8.14) [79]. The pooled analysis of four studies displayed that history of still birth/abortion was positively associated with PTB (AOR 3.93; 95% CI: 2.70-5.70) [10,37,57,64]. The pooled effects of four studies displayed that history of PTB increased the odds of PTB (AOR 3.45; 95% CI: 2.72-4.38) [10,46,64,69] (Fig.…”
Section: Reproductive Health Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 10 studies that assessed the association of short birth interval with preterm birth in Sub-Saharan African countries were included in this review. Five of the included studies were conducted in Ethiopia (18)(19)(20)(21)(22), two in Tanzania (23,24), two in Kenya (25,26), and one in Ghana (27). Of the ten studies two were cohort study (20,24), ve case-control (18,(21)(22)(23)27) and three cross-sectional (19,25,26).…”
Section: Included Study Characteristicsmentioning
confidence: 99%